Transformation of Principals' Leadership in Improving Teacher Professionalism and Classroom Management Effectiveness - Sulastri, Sulastri; Sahari, Sahari; Ayu Sulastri, Andi; Kasmah, Kasmah (DIDAKTIKA, 2023)
This study aims to describe and analyze the role of principal leadership in improving teacher professionalism on the effectiveness of classroom management at MI Amir Fil Jannah Tippulue. Using a descriptive qualitative approach, data was obtained through observation, in-depth interviews, and documentation of principals and classroom teachers. The results of the study show that school principals have carried out their strategic role as leaders through structured supervision, providing direction, and facilitating teacher competency improvement. The professionalism of teachers is reflected in the preparation of lesson plans, mastery of materials, and the use of varied learning methods. However, challenges are still found in terms of students' limited literacy skills, low motivation to learn, and support for a learning environment that is not optimal. Overall, the principal's leadership has proven to have a significant contribution in building teacher professionalism and more effective classroom management, although ongoing interventions are needed to address external constraints that affect student learning outcomes.